Supporting Historically Underrepresented Groups in STEM Higher Education: The Promise of Structured Mentoring Networks - Markle, Robert S.; Williams, Tyrslai M.; Williams, Kristen S.; deGravelles, Karin H.; Bagayoko, Diola; Warner, Isiah M. (Frontiers in Education, 2022)
Although institutions of higher education have placed a large emphasis on increasing the number of underrepresented minority (URM) students matriculating in higher education, the disparities in STEM retention and graduation rates between URM and non-URM students emphasize the dire need for increased support to help URM students navigate challenges including stereotype threat, impostor phenomenon, and lack of social connectedness that disproportionately affect URM students in majority-dominated fields. Prior research has demonstrated that structured mentoring has the potential to generate substantial improvements in academic, social, and career outcomes for URM STEM students. In particular, network-based mentoring approaches that allow for students to receive both professional and peer mentoring, as well as the opportunity to mentor other students, have demonstrated success in this realm. In this article, we discuss how the current state of academia often fails URM STEM scholars, review literature regarding the ways in which structured mentoring approaches can alleviate barriers to URM scholar success in STEM fields, and describe a model for implementing successful mentoring programs. Finally, we describe how the LS-PAC MODELS Center is utilizing an inter-institutional approach to close racial gaps in STEM academia via a network-based mentoring model and an innovative app-based mentoring platform designed to support URM STEM scholars at multiple career stages.